Depletion of Branched-Chain Ketoacid Dehydrogenase Kinase (BDK) Upregulates Insulin-Stimulated Glucose Uptake in Muscle Cells - Mann, Gagandeep (Curr Dev Nutr, 2021)
OBJECTIVES: Plasma levels of branched-chain amino acids (BCAAs) and their metabolites, branched-chain ketoacids (BCKAs) are increased in insulin resistance, a condition that can lead to type 2 diabetes mellitus (T2DM). BCAA catabolic enzymes are downregulated in diabetes and obesity. We previously showed that leucine and KIC suppressed insulin-stimulated glucose uptake in L6 myotubes. We have also shown that knocking down branched-chain ketoacid dehydrogenase (BCKD), an enzyme that decarboxylates BCKAs, suppressed insulin-stimulated glucose uptake. The objective of this study is to analyze how stimulating BCAA catabolic flux, by depleting branched-chain ketoacid dehydrogenase kinase (BDK), a negative regulator of BCKD, affects insulin sensitivity. We hypothesize that upregulating BCAA catabolism will increase insulin-stimulated glucose transport and attenuate insulin resistance. METHODS: L6 myoblasts were cultured in differentiation media for 4 days. On day 4 of differentiation, cells were transfected with control (SCR) or branched-chain ketoacid dehydrogenase kinase (BDK) siRNA oligonucleotides. Forty-eight hours later, myotubes were starved of serum- and amino acids for 3 hours then supplemented with or without KIC (200 mM) for 30 minutes. After, cells were incubated with or without insulin (100 nM) for 20 minutes. They were then harvested for immunoblotting or used for glucose transport assay. RESULTS: There was a 32% increase in insulin-stimulated glucose uptake with BDK depletion. KIC suppressed insulin-stimulated glucose uptake by 25% in control (SCR) cells; this suppression was attenuated in cells depleted of BDK. BDK depletion also reduced KIC-induced IRS-1(Ser612) phosphorylation by 64% but had no effect on Akt(Ser473) phosphorylation. CONCLUSIONS: BDK depletion increased insulin-stimulated glucose transport, and attenuated KIC-induced suppression of insulin-stimulated glucose uptake, suggesting that increasing BCKD activity can be a therapeutic strategy against insulin resistance. FUNDING SOURCES: Natural Science and Research Council (NSERC)